China's legal reform : towards the rule of law - Zou, Keyuan (Martinus Nijhoff Publishers, 2006)
China's entry into the World Trade Organization (WTO) has had a tremendous impact on the development and reform of China's legal system. This book focuses on the developments of China's legal system as well as its reform in the context of globalization. It covers various topics, including constitutional changes, law-based administration, and more.